use properties of operations to factor 8w+16 using GCF
a. 8(w+2)
b. 2(4w+8)
c. 6 (2w+10)
d. 4(2w+4)
11 answers
The correct answer is b. 2(4w+8)
Factor -27h+6 using the GCF
a. 3(9h+2)
b. 3(-9h+2)
c. 3(-9h+2)
d. 3(-9h-2)
a. 3(9h+2)
b. 3(-9h+2)
c. 3(-9h+2)
d. 3(-9h-2)
To factor -27h+6 using the GCF, we first need to find the greatest common factor (GCF) of -27 and 6. The GCF of -27 and 6 is 3.
Next, we divide each term in -27h+6 by the GCF of 3:
(-27h + 6) / 3 = -9h + 2
So the factored form of -27h+6 using the GCF is 3(-9h+2). The correct answer is a. 3(9h+2).
Next, we divide each term in -27h+6 by the GCF of 3:
(-27h + 6) / 3 = -9h + 2
So the factored form of -27h+6 using the GCF is 3(-9h+2). The correct answer is a. 3(9h+2).
expand and distribute -5(-3-11g)
a. 55g-15
b. -55g-15
c. -55g+15
d. 55g+15
a. 55g-15
b. -55g-15
c. -55g+15
d. 55g+15
To expand and distribute -5(-3-11g), we need to distribute the -5 to both terms inside the parentheses:
-5(-3-11g) = -5 * -3 - 5 * (-11g) = 15 + 55g = 55g + 15
So the correct answer is d. 55g + 15.
-5(-3-11g) = -5 * -3 - 5 * (-11g) = 15 + 55g = 55g + 15
So the correct answer is d. 55g + 15.
simplify by combining like terms 2/8x + 3/10y - 5/8x + 4/10 y
a. 14/18 xy
b -3/8x + 7/10y
c. 4/18xy
d. 7/10x + 7/8y
a. 14/18 xy
b -3/8x + 7/10y
c. 4/18xy
d. 7/10x + 7/8y
To simplify the expression 2/8x + 3/10y - 5/8x + 4/10y, we combine like terms by adding or subtracting coefficients that have the same variable.
First, let's combine the terms with x: 2/8x - 5/8x = (2-5)/8x = -3/8x
Next, let's combine the terms with y: 3/10y + 4/10y = (3+4)/10y = 7/10y
Therefore, the simplified expression is -3/8x + 7/10y.
The correct answer is b. -3/8x + 7/10y.
First, let's combine the terms with x: 2/8x - 5/8x = (2-5)/8x = -3/8x
Next, let's combine the terms with y: 3/10y + 4/10y = (3+4)/10y = 7/10y
Therefore, the simplified expression is -3/8x + 7/10y.
The correct answer is b. -3/8x + 7/10y.
evaluate when a=9, b=6
a-b/3
a. 6
b.9
c. 3
d. 1
a-b/3
a. 6
b.9
c. 3
d. 1
To evaluate the expression a-b/3 when a=9 and b=6, we substitute the given values into the expression:
a-b/3 = 9 - 6/3
Now, we simplify:
9 - 6/3 = 9 - 2 = 7
So, when a=9 and b=6, the value of a-b/3 is 7.
The correct answer is none of the given options.
a-b/3 = 9 - 6/3
Now, we simplify:
9 - 6/3 = 9 - 2 = 7
So, when a=9 and b=6, the value of a-b/3 is 7.
The correct answer is none of the given options.
evaluate the problem (a-b/3) when a=9, b=6
a. 6
b.9
c.3
d.1
a. 6
b.9
c.3
d.1
To evaluate the expression (a-b/3) when a=9 and b=6, we substitute the given values into the expression:
(a-b/3) = (9-6/3)
Now, we simplify:
(9-6/3) = (9-2) = 7
So, when a=9 and b=6, the value of (a-b/3) is 7.
The correct answer is none of the given options.
(a-b/3) = (9-6/3)
Now, we simplify:
(9-6/3) = (9-2) = 7
So, when a=9 and b=6, the value of (a-b/3) is 7.
The correct answer is none of the given options.